2017
DOI: 10.1016/j.neulet.2017.08.026
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine promotes increased freezing behavior in rats with experimental PTSD without changing brain glucose metabolism or BDNF

Abstract: Acute treatment with ketamine, an NMDA receptor antagonist, has been reported to be efficacious in treating depression. The goal of our study was to evaluate ketamine treatment in an animal model of another important psychiatric disease, post-traumatic stress disorder (PTSD). Fifty-eight male rats were initially divided into four groups: Control+Saline (CTRL+SAL), Control+Ketamine (CTRL+KET), PTSD+Saline (PTSD+SAL) and PTSD+Ketamine (PTSD+KET). To mimic PTSD we employed the inescapable footshock protocol. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 45 publications
2
19
0
Order By: Relevance
“…The hippocampus, amygdala, and hypothalamus showed increased BGluM, and enhanced activity of these regions may contribute to the enhanced fear memory observed in the ketamine group. A recent FDG-PET study reported that a post-fear conditioning ketamine injection (10 mg/kg, IP) increased fear behavior but did not alter BGluM in the hippocampus and amygdala of rats 20 . The authors measured BGluM 2 days after ketamine injection, whereas we measured BGluM immediately after the IV ketamine infusion in rats.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The hippocampus, amygdala, and hypothalamus showed increased BGluM, and enhanced activity of these regions may contribute to the enhanced fear memory observed in the ketamine group. A recent FDG-PET study reported that a post-fear conditioning ketamine injection (10 mg/kg, IP) increased fear behavior but did not alter BGluM in the hippocampus and amygdala of rats 20 . The authors measured BGluM 2 days after ketamine injection, whereas we measured BGluM immediately after the IV ketamine infusion in rats.…”
Section: Discussionmentioning
confidence: 95%
“…Results from preclinical studies investigating the effects of ketamine on fear memory in rodents are also inconsistent. Previous studies, utilizing intraperitoneal (IP) ketamine injection following fear conditioning, reported either improved 15 , 16 , worsened 17 20 , or no effects 21 , 22 on fear memory of rodents. For instance, mice that received a ketamine injection (30 mg/kg, IP) at 1 h or 1 week after fear conditioning showed no change 23 , while ketamine injected 1 day after fear conditioning facilitated fear memory extinction in rats 16 .…”
Section: Introductionmentioning
confidence: 99%
“…On a similar note, Saur et al (2017) classified individual rats as “extreme behavioral responders” (EBR) or “minimal behavioral responders” (MBR) according to the level of freezing on a situational reminder (SR) test 1 week after fear conditioning. The EBR rats that received ketamine showed heightened freezing on the SR test compared to the MBR rats [ 5 ]. Overall, the issue of individual variability is complex and difficult to study, as it requires a larger number of animals for statistical power and more in-depth behavioral characterization, along with the identification of biological markers.…”
Section: Effects Of Ketamine On Fear Memorymentioning
confidence: 99%
“…Ketamine (10 mg/kg, IP) given after the reactivation of contextual fear memory decreased fear memory reconsolidation while increasing BDNF mRNA levels in the prelimbic cortex in rats, indicating that upregulated BDNF diminishes fear reconsolidation [ 11 ]. By contrast, ketamine administration (10 mg/kg, IP) three days before a BDNF assay did not alter BDNF protein levels in the hippocampus or frontal cortex of rats, although the animals exhibited increased freezing behaviors one day after ketamine administration [ 5 ]. Moreover, although no behavioral outcome was measured, a ketamine infusion at an analgesic dose (10 mg/kg, IV, 2 h) increased BDNF protein in the amygdala of rats; this effect was dose-dependent and not seen with a 40 mg/kg infusion [ 40 ].…”
Section: Molecular Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation